2018 IEEE International Conference on Multimedia and Expo (ICME) 2018
DOI: 10.1109/icme.2018.8486579
|View full text |Cite
|
Sign up to set email alerts
|

Transformation on Computer-Generated Facial Image to Avoid Detection by Spoofing Detector

Abstract: Making computer-generated (CG) images more difficult to detect is an interesting problem in computer graphics and security. While most approaches focus on the image rendering phase, this paper presents a method based on increasing the naturalness of CG facial images from the perspective of spoofing detectors. The proposed method is implemented using a convolutional neural network (CNN) comprising two autoencoders and a transformer and is trained using a black-box discriminator without gradient information. Ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…From a reconstruction perspective, Nguyen et al [32] proposed a method to fool detectors by transforming computer-generated images into new images with encoding features of natural images. Peng et al [33] proposed a new generative adversarial network architecture, CGR-GAN, to resolve the problem of insufficient color, lack of texture details, and light changes of the work [32]. Peng et al [34] subsequently proposed the BDC-GAN structure to realize bidirectional conversion between natural and computer-generated images.…”
Section: B Image Anti-forensicsmentioning
confidence: 99%
“…From a reconstruction perspective, Nguyen et al [32] proposed a method to fool detectors by transforming computer-generated images into new images with encoding features of natural images. Peng et al [33] proposed a new generative adversarial network architecture, CGR-GAN, to resolve the problem of insufficient color, lack of texture details, and light changes of the work [32]. Peng et al [34] subsequently proposed the BDC-GAN structure to realize bidirectional conversion between natural and computer-generated images.…”
Section: B Image Anti-forensicsmentioning
confidence: 99%
“…Detector [47] A presentation attack is commonly used to bypass authentication systems using biometrics information (face, fingerprint, iris, and/or voice). Integration of a natural-CG image/video discriminator into the system before the authentication phase is one approach to preventing such attacks.…”
Section: Face Enhancement To Avoid Detection By Spoofingmentioning
confidence: 99%
“…We developed a method for avoiding detection by those such detectors like those mentioned above [47]. It works Table 1 Accuracy and detection rate before and after applying our proposed method on a custom database with images selected from MIT [52] and MS-Celeb database [53].…”
Section: Face Enhancement To Avoid Detection By Spoofingmentioning
confidence: 99%
“…Nguyen et al reported an attack method that transforms computer-generated (CG) images into natural images before feeding them into a facial authentication system [24]. The transformation model is trained using a generative adversarial network (GAN) [25].…”
Section: Related Workmentioning
confidence: 99%